PEMBERDAYAAN DAN BUDAYA ORGANISASI PADA HOME INDUSTRI PRODUK KREATIF DI BANGIL - Ambarwati, Titiek (Univesitas Muhammadiyah Malang, 2018)
Research objectives: (1) to analyze the empowerment of creative home industry products in Bangil. (2) to analyze the organizational culture in the home industry of creative products in Bangil. This research was conducted at home creative product industry in Bangil, the type of research used in this research is descriptive qualitative because the research is used to study a phenomenon in the object of research. While the object in the study of employees in the home industry creative products in Bangil. The method of data collection used in this research is the use of interview techniques and questionnaires (Questionnaire). Determination of the sample in this study was conducted by using the census method or total sampling with the number of respondents as many as 28 employees, especially the embroidery. Data analysis tool using Range Scale analysis to analyze employee empowerment and analyze organizational culture. The results of the research are as follows: for employee empowerment tendency on the dimension of access (opportunity) is high, the dimensions of participation tendency enough, the dimensions of decision making tendency and dimension of courage to take the risk of low tendency so that the average for employee empowerment done tendency is enough low. As for the organizational culture tendency in the dimensions of innovation is enough, the dimensions of openness tendency strong and the dimensions of cooperation tendency is enough so that it can be concluded the average organizational culture that applied cederung strong enough.